Modern Semi-Majolica and Glazed Ceramics from Rzeszów – Research on the Findings from the Archaeological Sites on 3 Maja Street - Trąbska, Joanna; Kocańda, Paweł; Trybalska, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Steadily growing collection of modern ceramics of the present Podkarpackie Voivodeship, has not yet been fully documented. Historical research demonstrates that Rzeszów, located on the communication route with Russia, occupied a very important position in trade relations with the East and West. The archaeometric study was performed on two fragments of semi-majolica plates and six fragments of glazed jugs, pots and tripod vessels. Vessels were made of fine-grained paste of smectite/illite, kaolinite/illite and kaolinite/illite/smectite clay. The richness of colours and shades is surprising. In the case of semi-majolica, the underglaze paintings were made with the use of frit pigments, while the overglaze ornament was made with the use of Pb-P-Ca-Si paste. ‘Slip-painting’ technique was also used. Glazes were coloured with iron, copper and cobalt compounds of various combinations and concentrations which provided different shades. In the case of semi-maiolica quartz-argillaceous primer with a potassium-bearing substance was applied, surfaces under glazes were covered with flux-bearing substances.
Keywords: Podkarpackie; Rzeszów; semi-maiolica; glazed pottery; SEM/EDS